(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
Metabolic syndrome (MetS) is a cluster of metabolic abnormalities that increases the risk of cardiovascular disease and type 2 diabetes. The burden of MetS is growing rapidly in Nigeria, driven by urbanization, sedentary lifestyles, and dietary changes. Early detection in at-risk populations is essential for prevention and management. The study aims to determine the prevalence of MetS and identify its predictors among patients attending Ring Road Specialist Hospital, Ibadan, using the National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III) criteria. A cross-sectional study was conducted among 200 participants recruited from the cardiovascular clinic, general outpatient department, and non-patient population working in the hospital. Sociodemographic, lifestyle, medical history, anthropometric, and biochemical data were collected. MetS was diagnosed according to NCEP-ATP III criteria. Statistical analysis included descriptive statistics, chi-square tests, and logistic regression to identify independent predictors. The prevalence of MetS was 51.6%, highest among cardiac patients (88%) and lowest in the non-patient group (12%). Hypertension and abdominal obesity were the most common components. Significant predictors of MetS included elevated HbA1c, high triglyceride levels, low HDL-C, and being in the cardiovascular clinic group. Logistic regression showed that elevated HbA1c (OR=3.01, p<0.001), triglycerides (OR=2.75, p=0.002), and low HDL-C (OR=2.18, p=0.015) independently predicted MetS. MetS is highly prevalent among patients in this secondary healthcare facility, particularly among those with existing cardiovascular disease. Routine screening using HbA1c and lipid profiles, combined with targeted lifestyle interventions, is recommended for early detection and management.